2017
DOI: 10.1039/c6ta10675g
|View full text |Cite
|
Sign up to set email alerts
|

One-pot surface engineering of battery electrode materials with metallic SWCNT-enriched, ivy-like conductive nanonets

Abstract: A facile and versatile surface engineering method based on metallic single-walled carbon nanotube (mSWCNT)-enriched, ivy-like conductive nanonets (mSC nanonets) for electrode materials was presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The as-prepared SWCNT/PANI catalysts showed significantly enhanced fuel cell efficiency [115]. Yoo et al [113] prepared ivy-like conductive m-SWCNTs nanonets using a onepot surface engineering strategy as displayed in Figure 12a. The authors employed Nd0.5Sr0.5CoO3 (NSC)-perovskite as a catalyst for the ORR/OER to test the feasibility of m-SWCNTs.…”
Section: Single-walled Carbon Nanotube-based Materialsmentioning
confidence: 99%
“…The as-prepared SWCNT/PANI catalysts showed significantly enhanced fuel cell efficiency [115]. Yoo et al [113] prepared ivy-like conductive m-SWCNTs nanonets using a onepot surface engineering strategy as displayed in Figure 12a. The authors employed Nd0.5Sr0.5CoO3 (NSC)-perovskite as a catalyst for the ORR/OER to test the feasibility of m-SWCNTs.…”
Section: Single-walled Carbon Nanotube-based Materialsmentioning
confidence: 99%
“…Semiconducting SWCNTs, if made denser, also begin to take up lithium at levels that are comparable to metallic SWCNTs [ 177 ]. One of the most recent studies showed that mSWCNT-enriched ivylike conductive nanonets were presented as a facile and versatile surface engineering method for battery electrode materials [ 178 ]. About five times as many lithium ions can be stored in metallic CNTs than in semiconducting CNTs.…”
Section: Applications Of Type and Chirality-separated Swcntmentioning
confidence: 99%
“…Recently, Yoo et al introduced a new class of m‐SWCNT enriched, ivy‐like conductive nanonets using a poly(9,9‐di‐ n ‐octylfluorenyl‐2,7‐diyl) (PFO)‐based sonication/filtration process. PFO—a common dispersing agent—shows a higher affinity for the s‐SWCNTs than for the m‐SWCNTs.…”
Section: Applications Of Sorted Carbon Nanotubesmentioning
confidence: 99%
“…d) ORR electrocatalytic activities of the pristine NSC, NSC@SWCNTs, and NSC@m‐SWCNTs. Reproduced with permission . Copyright 2017, The Royal Society of Chemistry.…”
Section: Applications Of Sorted Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation